AKTIVITAS ANTIOKSIDAN EKSTRAK BUAH PARIJOTO PADA BERBAGAI PH PENGOLAHAN PANGAN - Umar Hafidz Asy'ari Hasbullah; Rizki Bhakti Pertiwi; Isti Nurul Hidayah; Deby Andrianty (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2020)
Food processing can be done in the pH range from acid to base. This research aims to study the effect of various pH of food processing on antioxidant activity and total phenol extract of Parijoto fruit. Testing was carried out at pH 2, 4, 7, 8, and 10. Analysis of antioxidant activity using the DPPH radical scavenging activity method. Whereas phenol analysis uses the Folin Ciocalteu method. The results showed that the pH difference significantly affected the antioxidant activity and the total phenol extract of Parijoto fruit. Increasing pH causes an increase in antioxidant activity and in line with an increase in total phenol. Application of processing products from parijoto at higher pH will produce antioxidant activity and total phenols which tend to be higher.